2017
DOI: 10.1027/1618-3169/a000350
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Flexibility of Peripersonal Space

Abstract: The current study investigated individual differences in the flexibility of peripersonal space (i.e., representational space near the body), specifically in relation to trait claustrophobic fear (i.e., fear of suffocating or being physically restricted). Participants completed a line bisection task with either a laser pointer (Laser condition), allowing for a baseline measure of the size of one's peripersonal space, or a stick (Stick condition), which produces expansion of one's peripersonal space. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…As already mentioned, the size of PPS is modulated by the anxiety level of the individuals, with more anxious individuals showing a larger PPS [ 29 , 30 ]. Moreover, it has been shown that individuals with higher level of claustrophobia show a larger and less flexible PPS [ 24 , 69 ]. Regarding socio-communicative disorders several works have focused instead on the IPS.…”
Section: Resultsmentioning
confidence: 99%
“…As already mentioned, the size of PPS is modulated by the anxiety level of the individuals, with more anxious individuals showing a larger PPS [ 29 , 30 ]. Moreover, it has been shown that individuals with higher level of claustrophobia show a larger and less flexible PPS [ 24 , 69 ]. Regarding socio-communicative disorders several works have focused instead on the IPS.…”
Section: Resultsmentioning
confidence: 99%
“…This reflects the variability in PPS boundaries (or switch points) within the current sample. Studies have shown that individual differences in brain activity (Ferri et al 2015a) and emotional states such as anxiety (Sambo and Iannetti 2013) or fear (Taffou and Viaud-Delmon 2014;Ferri et al 2015b;de Haan et al 2016), and also anxiety disorders such as claustrophobia (Hunley et al 2017) can contribute to the variability observed in PPS boundaries. Although we did not specifically investigate this, it is possible that individual traits contributed to the large variability in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The slope in the analysis indexes the rate at which bias shifts rightward with increasing distance, a measure of the ‘‘size” of PPS. It has been previously shown that tool use produces a reduction of slope without a corresponding change in intercept (Longo and Lourenco 2006 ; Hunley et al 2017 ), indicating that closer and farther distances become less distinct with the farther distances being treated as if they are nearer in space—an extension of PPS. Moreover, we tested for a reduction of slope in the chin rest condition given that we hypothesized that the use of the chin rest would have expanded the PPS of the participants.…”
Section: Experiments 2: How General Is the Modulation Of Momentary Actmentioning
confidence: 99%
“…However, it has been shown that effort influences the peripersonal space representation and motor imagery using paradigms where the experimental hypotheses were, possibly, less transparent (Decety et al 1989 ; Lourenco and Longo 2009 ). Other studies have shown that emotion influences perception and representation of space with the fear of heights being associated with distorted perception of vertical distance (Jackson 2009 ; Stefanucci and Proffitt 2009 ; Teachman et al 2008 ), and claustrophobic fear associated with increased size of PPS representation (Lourenco et al 2011 ; Hunley et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%